1997
DOI: 10.1094/cchem.1997.74.6.750
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Granular Structures on the Pasting Behaviors of Starches

Abstract: Japonica (Tainung 67 [TNu67]) and waxy (Taichung 70 [TCW70]) rice, normal and waxy corn, and cross‐linked waxy rice and corn starches were used in an investigation of the influence of the granular structure on the pasting behavior of starch, using small amplitude oscillatory rheometry. Both normal corn and normal rice (TNu67) starches had the highest storage moduli (G′), followed by their cross‐linked versions; native waxy corn and rice starches had the lowest. Native waxy starches showed paste characteristics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
131
0
2

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 254 publications
(143 citation statements)
references
References 25 publications
10
131
0
2
Order By: Relevance
“…According to Tsai et al, (1997), this phenomenon occurs when most of the starch granules are fully swollen and other granules and dissolved polymers remain molecularly non-aligned within the field of friction of the Rapid Visco Analyzer (RVA).…”
Section: Resultsmentioning
confidence: 99%
“…According to Tsai et al, (1997), this phenomenon occurs when most of the starch granules are fully swollen and other granules and dissolved polymers remain molecularly non-aligned within the field of friction of the Rapid Visco Analyzer (RVA).…”
Section: Resultsmentioning
confidence: 99%
“…Reports have shown that the rigidity of swollen starch granules is the major factor determining the rheological properties of a starch paste or gel (Koo et al 2000). It is hypothesised that even though excess water causes leaching of amylose, which would increase the DR, annealing should increase the rigidity of the swollen granules, which would reduce the DR (Lii et al 1996;Tsai et al 1997 The average values ± standard deviation (n = 3); for each temperature set, values in the same column followed by different letters differed significantly (P < 0.05) Czech J. Food Sci., 34, 2016 (1): 79-86 doi: 10.17221/255/2015-CJFS annealing temperature and moisture content of the starch sample affected retrogradation behaviour.…”
Section: Dr Of Native Wheat Starch (Nws) and Annealed Starch (As)mentioning
confidence: 99%
“…In particular, it is one of the most important rheological indicators of the cooking quality and processing characteristics of rice. The amylose content and branch chain length distribution have also been found to have a substantial impact on the swelling and pasting properties of rice starches (Tsai et al, 1997;Jane et al, 1999). To examine the gelatinization characteristics of the four rice cultivars under analysis in this study, the swelling and thermal properties of their starches were measured using method of Li and Yeh (2001) and a differential scanning calorimeter, respectively.…”
Section: The Gelatinization and Swelling Of Rice Starchesmentioning
confidence: 99%